Contribution of Tourism Sector Taxes and Non-Metallic Mineral and Rock Taxes to Regional Original Revenue and Their Impact on the Regional Budget of Kuningan District 2013-2022 - Chairi Asyhad Yahya; Ayus Ahmad Yusuf (Cirebon International Journal of Economics and Business, 2024)
The management of Local Own-Source Revenue (PAD) plays a significant role in regional development. Analysis of the realization of Tourism Sector Taxes and Non-Metallic Mineral and Rock Taxes in Kuningan District during 2013-2022 shows annual fluctuations that are unstable. The aim of this research is to assess the contribution of both sectors to PAD as well as the impact of PAD on the Regional Revenue and Expenditure Budget (APBD) in Kuningan District. The General Allocation Fund (DAU) and Special Allocation Fund (DAK) variables are included as comparisons. This research method is quantitative with an associative approach. The research results show that the contribution of tourism sector taxes to PAD is 4.3%, while Non-Metallic Mineral and Rock Taxes contribute 1.92%. PAD and DAK significantly positively affect Kuningan's APBD (probability 0.01 and 0.002), whereas DAU is not significant (0.69 > 0.05). This research uses nonparametric tests with Eviews 12 as the analytical tool.